Notes linguistiques sur le « Salut d'amor » occitano-catalan. - Pigini, Noemi (Mot so razo Journal, 2022)
The article proposes a linguistic analysis of the Salut d'amor, a narrative text transmitted by the Catalan chansonnier Fa (Paris, BnF, esp. 487). This octosyllabic poem, which belongs to the tradition of the novas rimadas, is distinguished by a mixture of stylistic and literary elements derived from the Occitan troubadour tradition and also by images that recur in Catalan and French narrative works. Through an analysis of the scripta, we will try to summarise the most distinctive features of the Occitan-Catalan literary koinè to which the text belongs.